Delimitation of social economic entities - Francisco Javier Arrieta Idiakez (AECOOP Escuela de Estudios Cooperativos, 2015)
The main purpose of this research is to examine the essential aspects of the Social Economic Entities in Spain, following the coming into force of the 5/2011 Law. The study’s initial approach needs to focus in the background of these entities, acknowledging that the task to be carried out is not an easy one. Work then follows with a review of the 5/2011 Law, in order to better understand the structure that was used by the legislator to identify the ten entities that up to now can be accommodated under the Social Economy umbrella. In particular, article 5, which not only mentions the Entities of Social Economy, but also contains two open clauses, which cater for new entities being included in the future. Finally, the different kinds of entities are studied in detail, reviewing their main aspects and focusing on what makes them be closer, or move away from the Social Economy.